Enhancing Granulation in a Post-mucormycotic Maxillectomy Defect with Honey - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Infection with mucorales is a rare complication of uncontrolled diabetes. The infections are angio-invasive and have poor prognosis. The rhino-cerebral presentation of mucomycosis requires maxillectomies and aggressive antifungal therapy. The chances of recurrence remain high even with the best form of treatment. Honey has been used since ancient times as a dressing for wounds. It is said to aid wound healing by promoting the formation of granulation tissue. This property may be useful in cases where maxillectomy defects cannot be skin grafted.Patients and Methods:A review of literature on rhino-cerebral mucormycosis and the angiogenetic, antiseptic/healing characteristics of honey was carried out with the aim of highlighting its benefits in the intraoral perioperative management of craniomaxillofacial/rhino-cerebral mucormycosis. An illustrative case is presented to showcase these properties in the management of a 47-year-old diabetic male patient who presented with palatal mucormycosis, with treatment involving the therapeutic, surgical, and the reconstructive aspects of care.Results:Following intensive systemic antifungal use and surgical debridement, the patient developed extensive necrosis of the residual palatal defect which was refractory to eradication. The introduction of a pack impregnated with honey into the defect produced significant improvement in intraoral wound healing. This was accompanied by a rapid granulation of the defect resulting in a clean site.Conclusion:Topical honey dressings are recommended as an effective adjunct to conventional therapies for managing post-rhino-cerebral mucormycotic maxillectomy defects.